Synergistic effect of micro-nano fillers on reliability performance of hybrid electrically conductive adhesive - Adnan, Zainalfirdaus (2024)
In today's digital age, the escalating demand for efficient electronic technologies contrasts starkly with the global issue of electronic waste (e-waste) containing hazardous lead (Pb) solder. Consequently, there is a critical need for alternative materials in electronics interconnection technology, notably electrically conductive adhesives (ECA) based on polymer composites. Despite significant advancements in hybridizing various filler types in ECAs, systematic demonstration of material component optimization remains lacking. This gap jeopardizes the reliability performance of hybrid ECAs (HECA) due to polymer degradation under extreme environmental conditions of temperature and humidity. This research aims to establish an optimal HECA formulation with a low percolation threshold and enhanced reliability performance under extreme conditions, thereby investigating the failure mechanisms of HECA. The study employs a Design of Experiment (DOE) approach incorporating Analysis of Variance (ANOVA) and Response Surface Methodology (RSM) to optimize the formulation. Electrical and mechanical characterizations were conducted using a four-point probe with a Jandel RM3000+ test unit and a Hengzhun HZ-1003 universal testing machine (UTM), respectively. Samples underwent evaluation both before and after hygrothermal ageing at 85% relative humidity and 85°C for up to 504 hours. Morphological analysis utilized Scanning Electron Microscopy (SEM) and Field-Emission Scanning Electron Microscopy (FESEM). Rheological and thermal analyses were performed using an Anton Parr Rheometer and TGA-DSC1 analyser, respectively. The RSM indicated that the optimal HECA formulation achieved a 0.07 AgMF-MWCNT ratio, demonstrating enhanced electrical conductivity with a lower percolation threshold. Notably, no electrical degradation was observed over the ageing period for ratios of 0.07 and 0.17, underscoring their resilience under specified conditions. Despite epoxy cracking, micro-void formation, and delamination causing degradation, the HECA exhibited satisfactory mechanical reliability. Overall, the HECA formulation established at a 0.17 ratio in this study demonstrates superior electrical and mechanical reliability, making it well-suited for electronic packaging applications.